DESIGN ON THE RELIABILITY MODEL OF ORGANIZATION INFORMATION USING DYNAMIC BAYESIAN NETWORK - RAHMAN - NIM: 23215364 , ABDUL
An organization as a communicating entity is a dynamic system which people within organization can have access to information and speak to each other. Information derived from the ordinates can be accepted differently by subordinates. This occurs because of errors in the delivery of information, whether intentional or not. Since information is valuable resource for organization, it is therefore necessary to continuously analyze and re-examine how information spreads within organizations that could aid in the development of more effective structures for improving organizational functions and behaviors. Information flow covering the pattern, nature and direction of information disseminated is paramount importance in ensuring organization information reliability. Assurance of organization information reliability is expected to be a solution to maintain the accuracy of information within the organization to avoid misinformation. The concept of network organization is widely considered in research as a useful approach to increase flexibility and adaptive capacity of organizations, particularly in quality and sharing of information. This paper models the organization information reliability using Dynamic Bayesian Network (DBN) because of it meets aspects of pattern, nature and direction of information dissemination. The measures in the network organization concept is used for calculating DBN parameters.